Isolation and characterization of soluble human full‐length TDP‐43 associated with neurodegeneration. Issue 10 (9th July 2019) - Vega, Mirella Vivoli; Nigro, Alessia; Luti, Simone; Capitini, Claudia; Fani, Giulia; Gonnelli, Leonardo; Boscaro, Francesca; Chiti, Fabrizio
ABSTRACT: The involvement of transactivation response (TAR) DNA‐binding protein 43 (TDP‐43) in neurodegenerative diseases was revealed in 2006, when it was first reported to be the main component of the intracellular inclusions in patients with amyotrophic lateral sclerosis (ALS) and frontotemporal lobar degeneration. After 12 yr it is not yet possible to purify to a reasonable yield and in a reproducible manner a stable full‐length protein, which has limited so far the characterization of its structure, function, molecular interactors, and pathobiology. Using a novel protocol we have achieved the purification of the full‐length TDP‐43, with both a short pectate lyase B tag and a glutathione S‐transferase tag, which consisted in its expression in bacteria, solubilization from inclusion bodies, purification under denaturing conditions, refolding, and a final size exclusion chromatography (SEC) step. Differential scanning fluorimetry was used to find the best buffers and combination of additives to increase both its solubility and its stability. The protein is pure, as determined with electrophoresis, Western blotting, and mass spectrometry; properly refolded, as revealed by circular dichroism and fluorescence spectroscopies; functional, because it binds to DNA and protein partners; and stable to degradation and aggregation in a physiologic solution. Analyses with dynamic light scattering and SEC revealed that the protein is a dimer.—Vivoli Vega, M., Nigro, A., Luti, S., Capitini, C., Fani, G., Gonnelli, L., Boscaro, F., Chiti, F. Isolation and characterization of soluble human full‐length TDP‐43 associated with neurodegeneration. FASEB J. 33, 10780–10793 (2019). www.fasebj.org